Bioarchaeology Module Loading Please Hold. Recording Human Bioarchaeological Data from Portuguese Archaeological Field Reports - Seabra, Ana Lema (2016)
The Bioarchaeology Module as part of the Endovélico database maintained by the General Directorate for Cultural Heritage (DGPC) holds the record of archaeological and bioanthropological data. While primarily directed towards heritage management it has the potential to become a valuable tool to research by constituting a complementary record to the written archaeological field reports, making them more accessible for research. The poster communication aimed to expose the particular case of entering data into a database pertaining to information concerning archaeological human remains in archived Anthropological and Bioarchaeological Reports. These not only cover a wide scope of chronological periods and territorial space but also, as the main archaeological archive of Portuguese archaeological grey literature, it has a diverse collection of documentation from early 20th century reports to the present day. We explore the issues brought on by terminology, data and the reports themselves and explore how these might be addressed.